Pola Komunikasi Politik Kader Dalam Menindaklanjuti Koalisi Pimpinan Partai Menuju Pemilihan Presiden 2009 - Made Wilantara (Postgraduate of Jayabaya University, 2020)
This study aims to determine the Phenomenon Gerindra PDI Struggle and this seemed to be in a position opposite to the incumbent. From the context of political communication, the coalition of the two very interesting, because the pattern of political communication by party cadres. As the uniqueness of the surgical tool is the theory. Because of the cadre within the scope of the organization, then the knife is the study of communication theory of organization. Furthermore also equipped with leadership theory, organizational communication, the role of cadres in the political parties, as well as supporting study of the political coalition in the presidential election. The methodology is a case study, which focused on a dynamic case of a cadre of political communication patterns and the Party of Struggle PDI Gerindra at DPC level Bogor City. Or more accurately referred to as ‘situational analysis of case studies’, ie, qualitative data analysis methods that focus on specific cases that occur on the object of analysis. Data obtained by 3 methods, ie interviews, observation, and literature review. Interview data obtained as a comparison to the interpretation of researchers in connection with aspects of political communication patterns. Observations made in order to get an object of research and identification holistic communicators in it. While literature review as an analysis tool in the process of data interpretation. From the description, reduction, until the interpretation of data, obtained a dynamic phenomenon of communication patterns. Cadre communication patterns change in line with changes in public acceptance of the existence of leadership. Prabowo was marked as present as a figure who could fill the vacuum of leaders with a direct positive acceptance.